2015
DOI: 10.1097/bpo.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

Elbow Dislocation With an Associated Lateral Condyle Fracture of the Humerus

Abstract: Level II-retrospective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 13 publications
0
21
0
8
Order By: Relevance
“…Unusual types of dislocations, such as the terrible triad, divergent or convergent dislocations or with crossover of the radius and ulna, were also reported in the literature [13,17,21,22]. Silva et al [16] reported that posteromedial dislocation of the elbow was observed in most patients. All of the patients included in the present study had classical posterolateral or posteromedial dislocations occurred due to a fall.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Unusual types of dislocations, such as the terrible triad, divergent or convergent dislocations or with crossover of the radius and ulna, were also reported in the literature [13,17,21,22]. Silva et al [16] reported that posteromedial dislocation of the elbow was observed in most patients. All of the patients included in the present study had classical posterolateral or posteromedial dislocations occurred due to a fall.…”
Section: Discussionmentioning
confidence: 85%
“…The youngest reported patient with pure elbow dislocation in the literature was an 18 month-old child [4]. Limited numbers of studies discussing pure elbow dislocation in the paediatric age group have been published in the literature [1,3,7,8,10,16]. Di Gennaro et al [20] reported that dislocation of the elbow in children was a benign injury in the majority of cases and had a good prognosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Ellenbogenverletzungen im Kindesalter können schwerwiegende Verletzungen sein und zu dauerhaften Funktionsbeein trächtigungen führen [6,14,16,18] [8,19]. Im Folgen den werden die einzelnen Verletzungen mit entsprechenden Beispielen dargestellt.…”
unclassified